Cardiovascular, bone, and metabolic health in men with castrate-resistant prostate cancer treated with androgen deprivation: a matched cohort study. (2nd November 2022) - Khoshkar, Yashar; Vigneswaran, Hari T.; Eloranta, Sandra; Andersson, Therese M.-L.; Schain, Frida; Boman, Anton; Dahlkild, Martin; Liwing, Johan; Leval, Amy; Akre, Olof; Aly, Markus
Abstract: Background: Descriptive data on late effects associated with castrate-resistant prostate cancer (CRPC) are sparse. We aimed to define the timing and incidence of cardiovascular disease (CVD), fractures, and diabetes in a patient population with CRPC. Methods: In the population-based STHLM0 cohort 1464 men with CRPC were identified and matched with three men free from prostate cancer (PC) in the Stockholm region of Sweden. Kaplan–Meier estimates of net survival were used to describe time to CVD, fracture, and diabetes. Cox regression was used to compare incidence rates (IRRs) for the respective late effects. Cumulative incidence analyses of late effects in the presence of the competing risk of death were performed to estimate absolute risks. Results: The Kaplan Meier estimates demonstrated a higher net probability for CVD, fracture, and diabetes among men diagnosed with CRPC compared to the matched comparators. The IRRs were 1.94 (95% CI: 1.79–2.12) for CVD, 2.08 (95% CI: 1.70–2.53) for fracture, and 2.00 (95% CI: 1.31–3.05) for diabetes, respectively, comparing men diagnosed with CRPC to men free from PC. The cumulative incidence of CVD at 12 months of follow-up was higher in men diagnosed with CRPC compared to healthy controls regardless of age with a difference in cumulative incidence being 0.20 for men aged <65 and 0.11 for men aged >84. Conclusions: In this cohort, the incidence of CVD was significantly higher among men with CRPC compared to healthy controls. Despite having this end-stage disease this finding proves that clinicians must recognize this late effect in men diagnosed with CRPC to improve preventive actions. These men did not have a higher absolute risk of fractures and diabetes after accounting for deaths due to any cause compared to healthy controls.